Muscle-specific Bet1L knockdown induces neuromuscular denervation, motor neuron degeneration, and motor dysfunction in a rat model of familial ALS - Adam Eckardt; Charles Marble; Bradley Fern; Henry Moritz; Charles Kotula; Jiayi Ke; Clarisse Rebancos; Samantha Robertson; Hiroshi Nishimune; Masatoshi Suzuki; Masatoshi Suzuki (Frontiers in Neuroscience)
Amyotrophic lateral sclerosis (ALS) is a neuromuscular disease characterized by specific loss of motor neurons in the spinal cord and brain stem. Although ALS has historically been characterized as a motor neuron disease, there is evidence that motor neurons degenerate in a retrograde manner, beginning in the periphery at the neuromuscular junctions (NMJs) and skeletal muscle. We recently reported a vesicle trafficking protein Bet1L (Bet1 Golgi Vesicular Membrane Trafficking Protein Like) as a new molecule possibly linked to NMJ degeneration in ALS. In this study, we tested the hypothesis that Bet1L gene silencing in skeletal muscle could influence NMJ integrity, motor neuron function, and survival in a rat model of familial ALS (SOD1G93A transgenic). Small interfering RNA (siRNA) targeting the Bet1L gene was injected on a weekly basis into the hindlimb muscle of pre-symptomatic ALS and wild-type (WT) rats. After 3 weeks, intramuscular Bet1L siRNA injection significantly increased the number of denervated NMJs in the injected muscle. Bet1L knockdown decreased motor neuron size in the lumbar spinal cord, which innervated the siRNA-injected hindlimb. Impaired motor function was identified in the hindlimbs of Bet1L siRNA-injected rats. Notably, the effects of Bet1L knockdown on NMJ and motor neuron degeneration were more significant in ALS rats when compared to WT rats. Together, Bet1L knockdown induces denervation of NMJs, but also this knockdown accelerates the disease progression in ALS. Our results provide new evidence to support the potential roles of Bet1L as a key molecule in NMJ maintenance and ALS pathogenesis.